Gender gap in citations, h-index, and representation: Examining the highly cited authors across continents and disciplines in Google Scholar - Manuel Goyanes; Adrián Domínguez-Díaz; Beatriz Jordá; Luis de-Marcos (PLoS ONE, 2025)
This study investigates gender inequalities in academia by examining differences in representation, citations, and h-index between male and female highly cited researchers across disciplines and geographic regions. Using a unique dataset from Google Scholar, this study analyzes 21,509 highly cited authors across 191 fields and all continents. We examine gender disparities in citations, h-index, and representation while controlling for research productivity and career length to determine if female researchers experience different outcomes compared to their male counterparts. The findings reveal that women are significantly underrepresented among highly cited scholars globally (0.255 women per man) and receive fewer citations and have lower h-indexes than men in most regions and disciplines. However, after controlling for productivity and career length, female scholars are cited more than men in the pooled sample, Asia, Europe, and in two fields (natural sciences and exact sciences/physics). Despite this, women’s h-index remains significantly lower than men’s in all regions except Africa and South America, and in all fields except social sciences. This study highlights the persistence of gender inequalities in academic representation and long-term impact, as measured by the h-index. The results suggest that while citation rates for female researchers can match or exceed those of male scholars when productivity is controlled for, structural barriers continue to limit women’s long-term recognition in academia. This research contributes to the understanding of gender disparities among top researchers, showing that while citation parity is possible, significant gender gaps remain in overall academic representation and long-term recognition through h-index measures.